2020
DOI: 10.1017/sjp.2020.38
|View full text |Cite
|
Sign up to set email alerts
|

Parental Divorce and Interparental Conflict: Spanish Young Adults’ Attachment and Relationship Expectations

Abstract: This study focused on the associations between parental divorce and interparental conflict with young adults’ current attachment-related anxiety and avoidance, and romantic relationship expectations. The moderating effect of attachment history was also investigated. Using a sample of 1,078 Spanish young adults (544 women, 518 men; average age 21.4 years), our results confirmed that parental divorce is not associated with young adult children’s higher attachment anxiety and avoidance nor poorer romantic relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In fact, although some studies have found significant positive associations between parental divorce and children’s attachment, some other studies have not found such associations. For example, in a previous study [ 22 ], we found that parental divorce was not linked to higher attachment insecurity, as assessed through the attachment avoidance and anxiety dimensions. However, in the current study, which was conducted with the aim of shedding further light on these discrepancies, we did find some parental divorce process factors significantly associated with attachment-related anxiety and avoidance.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In fact, although some studies have found significant positive associations between parental divorce and children’s attachment, some other studies have not found such associations. For example, in a previous study [ 22 ], we found that parental divorce was not linked to higher attachment insecurity, as assessed through the attachment avoidance and anxiety dimensions. However, in the current study, which was conducted with the aim of shedding further light on these discrepancies, we did find some parental divorce process factors significantly associated with attachment-related anxiety and avoidance.…”
Section: Discussionmentioning
confidence: 77%
“…In this vein, although several studies have consistently concluded that adult children from divorced families, and especially women, are more likely to be insecurely attached than their counterparts from non-divorced families [ 9 , 13 , 18 , 19 ], the results are mixed. Furthermore, some other studies have failed to replicate these results, by not finding significant associations between parental divorce and adult children’s attachment-related strategies or representations [ 20 , 21 , 22 , 23 ]. These controversial results regarding the effects of parental divorce on adult children’s attachment-related representations might be because most of these studies have analyzed parental divorce as a single dichotomous variable by uniquely asking participants whether their parents were separated or divorced [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite previous research about the negative consequences of parental divorce (Cui & Fincham, 2010), there was no association between parents’ separation and marital beliefs. In Spain, parental divorce does not seem to affect relationship expectations (Smith-Etxeberria et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we studied the impact of destructive IPC on child development. Evidence has suggested that parental divorce might relieve children of the stress resulting from continued exposure to high levels of conflict (Smith-Etxeberria et al, 2020). Although the percentage of divorce among Chinese parents is increasing over time, in general, marriages remain stable, with more than 93% of parents not getting divorced in China (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%